Analysis of Communication and Information Science Education Inclusivity in a STEM Environment in Zimbabwe - Alois Matorevhu (International Journal of Trends in Mathematics Education Research, 2018)
Communication and Information Science (CIS) can be effectively applied in a STEM environment if ICT is accessible to people including those who are visually impaired (VI). This is premised on that Information and Communication Technology (ICT) has invaded every part of society, from home, industry and social life, as the world moves rapidly into digital media.  One way of ensuring the effective inclusion of VI people in communication and Information Science is to have an education system from preschool, secondary through to tertiary which has inclusive ICT education. Apart from engendering CIS, ICT promotes/enhances student-centered learning consistent with STEM objectives. Through Zimbabwe’s education system, the visually impaired (VI) people like anybody else, need to understand and apply ICT as a tool to aid their learning, professional development, and a means of socializing. What is questionable is whether the education system of Zimbabwe from preschool, prepares VI people to be effective users of ICT as STEM objectives suggest.  In order to gain insight, curricula documents for a selected teachers’ college T and Ministry of Primary and Secondary Education curriculum documents were analyzed.  Also, data was generated through interviews and focus group discussion with VI pre-service teachers at teachers’ college T. The interviews and focus group discussions aimed to generate data through VI pre-service teachers’ reflections on their primary and secondary school days, juxtaposed with their current experience during teacher training with respect to inclusivity on use of ICT as a tool for teaching and learning, aiding personal learning and social life interactions. All the 10 VI pre-service teachers involved in the study concurred that if ICT learning and application begins as early as primary level, one is bound to develop high competence and confidence in ICT use. However, a very supportive environment, morally and materially, was seen as crucial in developing high competence and confidence levels of VI persons in using ICT for learning and in social life.